Evolution of the α‐BaMg(CO3)2 low‐temperature superstructure and the tricritical nature of its α–β phase transition. Issue 5 (20th September 2017) - Ende, Martin; Effenberger, Herta; Miletich, Ronald
Abstract : Using a high‐sensitivity silicon detector and a micro‐focus source, the norsethite [BaMg(CO3 )2 ] low‐temperature superstructure has been tracked across the temperature‐driven α–β phase transition using single‐crystal diffraction experiments. Systematic analysis of physical potential order parameters reveals the structure‐related driving force and that the transition is tricritical in nature. Abstract : The crystal structure of the synthetic double carbonate norsethite [BaMg(CO3 )2 ] has been reinvestigated using X‐ray diffraction data within the temperature range 100–500 K using a high‐sensitivity PILATUS pixel detector. The previously assumed positional shift of the crystallographically unique oxygen atom is confirmed. The shift is associated with a coupled rotation of symmetry‐equivalent carbonate groups. It was possible to follow the shift using high‐accuracy experiments under varying temperature conditions between 100 K and the critical transition temperature occurring at T c = 363 ± 3 K. The transition of the α‐form (space group R c ; below T c ), which represents a superstructure of the β‐form (space group R m, with c ′ = c /2; above T c ) was studied in detail. The tricritical order character of this displacive phase transition was verified by tracking the intensities of the recorded superstructure reflections ( l = 2 n + 1) from single‐crystal diffraction and using high‐precision lattice parameters obtained from powder diffraction in transmission geometry. Thermodynamic properties suggest both rotation of the CO3 group and a coordination change of the BaO12 coordination polyhedra as the order parameters driving the temperature‐dependent α–β phase transition. Nevertheless, a detailed structural analysis reveals the coordination change of the barium atoms to be the main driving force for the observed transformation.